Bioremediasi Fosfat Limbah Detergen dan Model Kinetika Reaksi SPIROFILTER Berbasis Spirogyra porticalis (O.F. Mueller) Cleve - Siswanti, Dwi Umi; Rain, Oryza Enwiera; Sinambela, Benn Gerson Juan Moreno (Fakultas Biologi Universitas Gadjah Mada, 2025)
Wastewater has become a source of environmental problems caused by the content of chemicals that are harmful to the environment, including detergent waste. Detergent is a cleaning agent that contains surfactants, phosphate compounds, and other additives. Efforts to handle this detergent waste have been carried out communally or on a large scale in a reactor called IPAL (Wastewater Treatment Plant). However, no effective household-scale IPAL prototype has been found to restore wastewater quality to raw water that can be reused. So a prototype IPAL was built called SPIROFILTER which combines the filtration process by zeolite, activated charcoal, and cotton as well as hyperaccumulation by Spirogyra porticalis. This study aims to determine the role of S. porticalis, analyze wastewater quality, analyze the growth of S. porticalis, and determine the reaction kinetics model (PFO or PSO) in the absorption of phosphate in wastewater that has been filtered with SPIROFILTER. The research design was in the form of measuring the growth of S. porticalis and the quality of water before filtration (control), water after the 3rd day, and water after the 5th day. The parameters measured were temperature, pH, salinity, total phosphorus, total ammonia, BOD, COD, number of water germs, and chlorophyll content. This study used a UV-vis spectrophotometer and AAS for water quality testing. SPIROFILTER was an aquarium measuring 40x60x20 cm3 to which 132 mL of detergent was added in 22 liters of water. The results of the study proved that S. porticalis acted as a hyperaccumulator, the quality of water filtered by SPIROFILTER met water quality standards, the growth of S. porticalis remained optimum in detergent waste environmental conditions, the kinetic model of the phosphorus binding reaction from detergent waste used the Pseudo Second Order model in SPIROFILTER. Keywords: Detergent waste, Reaction kinetics, SPIROFILTER, Spirogyra porticalis, Water quality standards